Enzyme-assisted extraction (EAE): efficient and effective green extraction on turmerik (Curcuma longa L.) and temulawak (Curcuma xanthorriza Roxb.) rhizomes for higher yield and content of curcumin - Dia Septiani; Marsah Rahmawati Utami; Mally Ghinan Sholih; Tiara Nurayuni; Syifa Khairunnisa (Universitas Ahmad Dahlan, 2026)
Curcumin, as the main active compound in Zingiberaceae plants, turmeric and temulawak, with various health benefits. That active compound generally exists in low concentrations, thus an effective and efficient method is needed to extract these compounds, such as Enzyme Assisted Extraction (EAE), one of which involves cellulase enzyme. This study aims to use the Enzyme Assisted-Extraction (EAE) method with cellulase enzyme in the extraction of curcumin from turmeric and temulawak plants, and to evaluate the extraction yield and efficiency of extract, comparing the curcumin content in turmeric and temulawak extracts between EAE and conventional maceration extraction method. The research was conducted using a Randomized Block Design (RBD) experiment with variations in temperature (45°, 50°, 55℃), time (1 hour, 2 hours, 3 hours), and enzyme concentration of 6%. The research stages included determining the water and ash content in the raw materials, water content in the extracts, extraction using maceration and EAE methods, determination of extract yield, extract purification, phenol screening, analysis of curcumin content using UV-Vis Spectrophotometry, and statistical analysis using the Mann-Whitney test. The results showed that the use of cellulase enzyme in the extraction process of turmeric and temulawak successfully increased the extract yield and curcumin content. The highest yield was obtained in turmeric at 34.24%± 0.038, and the highest curcumin content was achieved at a temperature of 45˚C for 2 hours, reaching 56.86% ± 0.090. Meanwhile, in temulawak, the highest yield was 53.11%± 0.385, and the highest curcumin content was obtained at a temperature of 50˚C for 2 hours, reaching 54.10% ± 0.100. There was an increase in curcumin content in turmeric and temulawak EAE extract compared to the conventional maceration extraction method. Statistical analysis using the Mann-Whitney test (p < 0.05,) indicating a significant difference between the EAE and conventional maceration extraction method.